2019
DOI: 10.1093/jac/dkz152
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with antibiotic prescribing for adults with acute conditions: an umbrella review across primary care and a systematic review focusing on primary dental care

Abstract: Introduction One way to slow the spread of resistant bacteria is by improved stewardship of antibiotics: using them more carefully and reducing the number of prescriptions. With an estimated 7%–10% of antibiotic prescriptions globally originating from dental practices and up to 80% prescribed unnecessarily, dentistry has an important role to play. To support the design of new stewardship interventions through knowledge transfer between contexts, this study aimed to identify factors associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 35 publications
4
67
0
7
Order By: Relevance
“…With antibiotic resistance being recognised as an important public-health threat worldwide [ 33 ] and physicians being seen as crucially responsible for antibiotic misuse, one strength of this study is having detected that, in many settings, physicians display important shortcomings, dating back to the time of their education, in the treatment of highly common infections. We feel that these results are particularly important, since these shortcomings are easily remediable at this early stage of a medical student’s education: it is simply necessary for the educational and/or health authorities (from a global level all the way down to those responsible for individual educational centres) to ensure that their educational priorities are proportional to the impact which antibiotic misuse has on public health around the world.…”
Section: Discussionmentioning
confidence: 99%
“…With antibiotic resistance being recognised as an important public-health threat worldwide [ 33 ] and physicians being seen as crucially responsible for antibiotic misuse, one strength of this study is having detected that, in many settings, physicians display important shortcomings, dating back to the time of their education, in the treatment of highly common infections. We feel that these results are particularly important, since these shortcomings are easily remediable at this early stage of a medical student’s education: it is simply necessary for the educational and/or health authorities (from a global level all the way down to those responsible for individual educational centres) to ensure that their educational priorities are proportional to the impact which antibiotic misuse has on public health around the world.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published umbrella review on antibiotic use for adults in primary care (though focused on dental care) identified several factors that appear to affect prescribing behaviors in HICs, such as socio-cultural context, financial incentives, personal beliefs, patients' attitudes, and AMR awareness [80]. Similar considerations likely apply to prescription practices in LMICs, although a deeper understanding of underlying determinants remains challenging.…”
Section: Plos Medicinementioning
confidence: 99%
“…Patients may see clinicians with different practice patterns regarding antibiotic prescription (either in the same practice or when visiting multiple practices), leading to an expectation for antibiotics. In response to a desire to improve patient satisfaction scores tied to reimbursement or to improve patient critiques on social media sites tied to patient recruitment, clinicians may prescribe antibiotics in an attempt to improve patient satisfaction …”
Section: Drivers Of Inappropriate Antibiotics For Older Adults In Ambmentioning
confidence: 99%